Allele Sorting as a Novel Approach to Resolving the Origin of Allotetraploids Using Hyb-Seq Data: A Case Study of the Balkan Mountain Endemic Cardamine barbaraeoides - Šlenker, Marek; Kantor, Adam; Marhold, Karol; Schmickl, Roswitha; Mandáková, Terezie; Lysak, Martin A.; Perný, Marián; Caboňová, Michaela; Slovák, Marek; Zozomová-Lihová, Judita (Frontiers in Plant Science, 2021)
Mountains of the Balkan Peninsula are significant biodiversity hotspots with great species richness and a large proportion of narrow endemics. Processes that have driven the evolution of the rich Balkan mountain flora, however, are still insufficiently explored and understood. Here we focus on a group of Cardamine (Brassicaceae) perennials growing in wet, mainly mountainous habitats. It comprises several Mediterranean endemics, including those restricted to the Balkan Peninsula. We used target enrichment with genome skimming (Hyb-Seq) to infer their phylogenetic relationships, and, along with genomic in situ hybridization (GISH), to resolve the origin of tetraploid C. barbaraeoides endemic to the Southern Pindos Mts. (Greece). We also explored the challenges of phylogenomic analyses of polyploid species and developed a new approach of allele sorting into homeologs that allows to identify subgenomes inherited from different progenitors. We obtained a robust phylogenetic reconstruction for diploids based on 1,168 low-copy nuclear genes, which suggested both allopatric and ecological speciation events. In addition, cases of plastid-nuclear discordance, in agreement with divergent nrDNA copy variants in some species, indicated traces of interspecific gene flow. Our results also support biogeographic links between the Balkan and Anatolian-Caucasus regions and illustrate the contribution of the latter region to high Balkan biodiversity. An allopolyploid origin was inferred for C. barbaraeoides, which highlights the role of mountains in the Balkan Peninsula both as refugia and melting pots favouring species contacts and polyploid evolution in response to Pleistocene climate-induced range dynamics. Overall, our study demonstrates the importance of a thorough phylogenomic approach when studying the evolution of recently diverged species complexes affected by reticulation events at both diploid and polyploid levels. We emphasize the significance of retrieving allelic and homeologous variation from nuclear genes as well as multiple nrDNA copy variants from genome skim data.